Analisis dan Perancangan Sistem Informasi Manajemen Rumah Sakit Berbasis Website Pada Rumah Sakit Umum Kambang Kota Jambi - Ardiansyah, Ardiansyah; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2021)
KAMBANG GENERAL HOSPITAL IN JAMBI still used conventional method, namely in getting number of queue, the information of doctor’s schedule, and the number of patients who had registered. The information had been got by the patients were only from various media or went to the hospital directly. So that the informations did not complete. The patients who got number of queue for checking health, should go to hospital and knowing the doctor’s schedule and number of patients who had registered, making the system did not work well and made the process was long. It was done an analysis and design of web based for solving the problems. This analysis was used for uneffectivities and lackness in information system could be minimize and could be easy to be accessed by the patients and also for the other societies as patients. The method would be used in developing system was Waterfall method. Meanwhile the tools of the model of system which was used by the writer was Use Case Diagram, Activity Diagram and Class Diagram. By making prototype in giving the information the doctor’s schedule, the number of patients and other important activities in hospital and solving the old system. In this research would be hope, it could develope and implemented in the real system and would be better again.